Corporate Behavior in Adjusting to Capital Structure and Dividend Targets: An Econometric Study - Jalilvand, Abolhassan; Harris, Robert S. (Journal of Finance, 1984)
This study of financing decisions by U.S. corporations examines the issuance of long term debt, issuance of short term debt, maintenance of corporate liquidity, issuance of new equity, and payment of dividends. Given costs and imperfections inherent in markets, a firm's financial behavior is characterized as partial adjustment to long run financial targets. Individual firm data are used so that speeds of adjustment are allowed to vary by company and over time. The results suggest that financial decisions are interdependent and that firm size, interest rate conditions, and stock price levels affect speeds of adjustment.